Implementation of the Qiroati Method in Improving the Reading of the Qur'an at MTs Darun Nahwi Singajaya - Sovi Hafidoh (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The location of this research was conducted at MTs Darun Nahwi Singajaya, Indramayu. Previously, MTs Darun Nahwi still used the idarah/tadarusan method, because many teachers complained because they felt it was difficult in the assessment and evaluation process of students until the researcher planned to replace the idarah method with the qiro'ati method in learning the Qur'an, with this method it turned out to attract children's interest in learning to read the Qur'an. This study aims to determine how the implementation of the qiro'ati method improves the ability to read the Qur'an at MTs Darun Nahwi. The type of research used is quantitative research. The data analysis technique uses data collection carried out using observation, interview and documentation techniques. The subjects in this study were the principal and staff of the teaching staff, the objects of the study were students of MTs Darun Nahwi. The results of this study are 1. The application of the qiro'ati method in learning to read the Qur'an at MTs Darun Nahwi is quite good, seen from the increase in reading the Qur'an compared to before 2. The teaching system in the qiro'ati method is: Practical, simple, little by little, and alert to wrong readings 3. The inhibiting factors of the qiroati method at MTs Darun Nahwi are the lack of teacher ability in mastering the class, the imbalance between the number of teachers and the number of students, limited time allocation, and the lack of adequate facilities and infrastructure.